2021
DOI: 10.3389/fimmu.2021.656885
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomics Uncovers Distinct Contributions From Splicing Regulatory Proteins to the Macrophage Innate Immune Response

Abstract: Pathogen sensing via pattern recognition receptors triggers massive reprogramming of macrophage gene expression. While the signaling cascades and transcription factors that activate these responses are well-known, the role of post-transcriptional RNA processing in modulating innate immune gene expression remains understudied. Given their crucial role in regulating pre-mRNA splicing and other RNA processing steps, we hypothesized that members of the SR/hnRNP protein families regulate innate immune gene expressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…In mice, a virulent dam mutant Salmonella vs. WT Salmonella infection revealed ISG role in host response [59]. Although IFN-/ does not directly activate the MX1 gene, evidence demonstrates that it is involved in the host response to Salmonella infection [59,60]. In uninfected and Salmonella-infected macrophages, serine-arginine regulates the expression of numerous gene regulations, with several essential innate immunity genes (Nos2, MX1) relying on several SR/hnRNPs to maintain repression [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, a virulent dam mutant Salmonella vs. WT Salmonella infection revealed ISG role in host response [59]. Although IFN-/ does not directly activate the MX1 gene, evidence demonstrates that it is involved in the host response to Salmonella infection [59,60]. In uninfected and Salmonella-infected macrophages, serine-arginine regulates the expression of numerous gene regulations, with several essential innate immunity genes (Nos2, MX1) relying on several SR/hnRNPs to maintain repression [60].…”
Section: Discussionmentioning
confidence: 99%
“…Although IFN-/ does not directly activate the MX1 gene, evidence demonstrates that it is involved in the host response to Salmonella infection [59,60]. In uninfected and Salmonella-infected macrophages, serine-arginine regulates the expression of numerous gene regulations, with several essential innate immunity genes (Nos2, MX1) relying on several SR/hnRNPs to maintain repression [60]. At the host-parasite interface, C. parvum and intestinal epithelial cells interact by transmitting effector molecules from the host cell and the parasite [61].…”
Section: Discussionmentioning
confidence: 99%
“…RNA splicing is one way among others to ensure the proper timing and intensity of ISG expression. Splicing regulation involves one or more splicing factors acting like a regulatory node, as illustrated by heterogeneous nuclear RiboNucleoProteins (hnRNPs) ( 177 ). hnRNPs are complexes comprising typical RNA-binding and modular proteins mostly present in the nucleus ( 178 ).…”
Section: Role Of Rbps In Rna Processing During Innate Immunitymentioning
confidence: 99%
“…Proinflammatory cytokines, particularly TNF-α and IFN-γ have been shown to be important in controlling R. equi infection in foals. To begin to define the nature of the macrophage innate immune response to R. equiinfection, we set out to compare innate immune responses in primary macrophages derived from both foals and mice to those elicited in RAW 264.7 cells, a genetically tractable macrophage-like cell line in which our lab has developed tools to knockdown or -out key components of the innate immune system [27,[41][42][43][44]. In past studies using RAW 264.7 cells with Mtb, Salmonella, and Listeria, we have found that activation of both TLR and cytosolic nucleic acid sensing pathways induce transcriptional responses comparable to primary macrophages [27,41,[43][44][45].…”
Section: R Equi Induces Pro-inflammatory Cytokine Expression During Macrophage Infectionmentioning
confidence: 99%
“…To begin to define the nature of the macrophage innate immune response to R. equiinfection, we set out to compare innate immune responses in primary macrophages derived from both foals and mice to those elicited in RAW 264.7 cells, a genetically tractable macrophage-like cell line in which our lab has developed tools to knockdown or -out key components of the innate immune system [27,[41][42][43][44]. In past studies using RAW 264.7 cells with Mtb, Salmonella, and Listeria, we have found that activation of both TLR and cytosolic nucleic acid sensing pathways induce transcriptional responses comparable to primary macrophages [27,41,[43][44][45]. To determine whether R. equi infection followed a similar paradigm, we first compared pro-inflammatory cytokine induction at the transcript level in both primary murine bone marrow derived macrophages (BMDMs) and equine bronchoalveolar cells (consisting of 85% macrophages) (S1A Fig) . Primary cells were infected with virulent R. equi (ATCC 330701+) at a multiplicity of infection (MOI) of 5.…”
Section: R Equi Induces Pro-inflammatory Cytokine Expression During Macrophage Infectionmentioning
confidence: 99%